-2x-8(-4x-6)=-5x+6(7x+8)

Simple and best practice solution for -2x-8(-4x-6)=-5x+6(7x+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x-8(-4x-6)=-5x+6(7x+8) equation:



-2x-8(-4x-6)=-5x+6(7x+8)
We move all terms to the left:
-2x-8(-4x-6)-(-5x+6(7x+8))=0
We multiply parentheses
-2x+32x-(-5x+6(7x+8))+48=0
We calculate terms in parentheses: -(-5x+6(7x+8)), so:
-5x+6(7x+8)
We multiply parentheses
-5x+42x+48
We add all the numbers together, and all the variables
37x+48
Back to the equation:
-(37x+48)
We add all the numbers together, and all the variables
30x-(37x+48)+48=0
We get rid of parentheses
30x-37x-48+48=0
We add all the numbers together, and all the variables
-7x=0
x=0/-7
x=0

See similar equations:

| 1-6(8-3x)=29 | | 6x+21=1/2(17x+28) | | 93=7+4(6x-5) | | 81z4-16=0 | | 4p/5+3=10 | | n(0.56)+9(0.56)=3 | | 4p=5+3=10 | | -4-8x=10 | | 9(a)=5 | | 3(1+p)=-5p+1 | | 0.2x=58 | | -3x+35=x+3 | | 37+87+z=180 | | x4=(2⋅x−3)2 | | 2x+x+130=180 | | 4(5x+2)=3x+8 | | P-4q+8q= | | x+16=-2x+1 | | x+12=-2x-12 | | x+30-90=180 | | 21b+7=5(b+1) | | 6x-18+6x-18+3x+9+3x+9=180 | | 17-9x=8x | | v-3.65=9.57 | | 6x-18x2+3x+9x2=180 | | 4x-10-x=40 | | u-7.47=6.2 | | 3936*x=32 | | u+7.95=9.31 | | 40p+2=14 | | 11-5x-3x-4x=18 | | 6x+2x+1+4=8x+5 |

Equations solver categories